Developing Narrative Texts with Mystery Elements for Grade 10 Students - Intan Fandini; Totoh Tauhidin Abas; Fela Dafitri (Universitas Islam Negeri Palopo, 2026)
This study aims to develop a narrative text with mystery elements as a reading instructional material for Grade 10 students and to examine student responses toward the developed material. The study employed a Research and Development (R&D) approach adapted from the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research was motivated by the limited availability of engaging reading materials that align with the interests and learning needs of Grade 10 senior high school students. The narrative text was developed based on genre-based theory and materials development principles, incorporating mystery elements such as tension-building conflicts, unexpected events, and clues scattered throughout the storyline. A total of 37 Grade 10 students at a senior high school in Indonesia participated as research subjects. Data were collected through expert validation sheets and student response questionnaires. The results indicated that the developed narrative text was declared valid and appropriate by a language expert (87.5%) and a materials development expert (85.0%). Furthermore, students demonstrated highly positive responses with a mean questionnaire score of 82.3%, indicating that the text was engaging, comprehensible, and motivating. The study concludes that a narrative text with mystery elements can serve as an effective and engaging reading instructional material for Grade 10 senior high school students.